Modernity and the Construction of Sacred Space - French, Aaron J.; Waldner, Katharina (SpatioTemporality / RaumZeitlichkeit, 2024)
This book explores the intersection of modern architecture and religious studies. It focuses on rethinking the concept of sacred space in a modern context, bringing together scholars from diverse fields into an interdisciplinary dialogue that is both practical and analytic. Topics include the temples of New Religious Movements, new church designs in Rwanda, sacred spaces for festival culture, the use of space in modern magical practice, and more